Increased Circulating Adiponectin in Response to Thiazolidinediones: Investigating the Role of Bone Marrow Adipose Tissue - Sulston, Richard J.; Learman, Brian S.; Zhang, Bofeng; Scheller, Erica L.; Parlee, Sebastian D.; Simon, Becky R.; Mori, Hiroyuki; Bree, Adam J.; Wallace, Robert J.; Krishnan, Venkatesh; MacDougald, Ormond A.; Cawthorn, William P. (Frontiers in Endocrinology, 2016)
BACKGROUND: Bone marrow adipose tissue (MAT) contributes to increased circulating adiponectin, an insulin-sensitising hormone, during caloric restriction, but whether this occurs in other contexts remains unknown. The anti-diabetic thiazolidinediones (TZDs) also promote MAT expansion and hyperadiponectinaemia, even without increasing adiponectin expression in white adipose tissue (WAT). OBJECTIVES: To test the hypothesis that MAT expansion contributes to TZD-associated hyperadiponectinemia, we investigated effects of rosiglitazone, a prototypical TZD, in wild-type (WT) or Ocn-Wnt10b mice. The latter resist MAT expansion during caloric restriction, leading us to postulate that they would also resist this effect of rosiglitazone. DESIGN: Male and female WT or Ocn-Wnt10b mice (C57BL/6J) were treated with or without rosiglitazone for 2, 4 or 8 weeks, up to 30 weeks of age. MAT content was assessed by osmium tetroxide staining and adipocyte marker expression. Circulating adiponectin was determined by ELISA. RESULTS: In WT mice, rosiglitazone caused hyperadiponectinemia and MAT expansion. Compared to WT mice, Ocn-Wnt10b mice had significantly less MAT in distal tibiae and sometimes in proximal tibiae; however, interpretation was complicated by leakage of osmium tetroxide from ruptures in some tibiae, highlighting an important technical consideration for osmium-based MAT analysis. Despite decreased MAT in Ocn-Wnt10b mice, circulating adiponectin was generally similar between WT and Ocn-Wnt10b mice; however, in females receiving rosiglitazone for 4 weeks, hyperadiponectinemia was significantly blunted in Ocn-Wnt10b compared to WT mice. Notably, this was also the only group in which tibial adiponectin expression was lower than in WT mice, suggesting a close association between MAT adiponectin production and circulating adiponectin. However, rosiglitazone significantly increased adiponectin protein expression in WAT, suggesting that WAT contributes to hyperadiponectinemia in this context. Finally, rosiglitazone upregulated uncoupling protein 1 in brown adipose tissue but this protein was undetectable in tibiae, suggesting that MAT is unlikely to share thermogenic properties of brown adipose tissue. CONCLUSIONS: TZD-induced hyperadiponectinemia is closely associated with increased adiponectin production in MAT, but is not prevented by the partial loss of MAT that occurs in Ocn-Wnt10b mice. Thus, more robust loss-of-MAT models are required for future studies to better establish MAT’s elusive functions, both on an endocrine level and beyond.